Navigating Airway Challenges in a Case of Neurofibromatosis: An Anaesthetic Perspective - Sandip Baheti; Supriya Gholap; Amala Kale (Journal of Clinical and Diagnostic Research)
Neurofibromatosis type 1 (NF1) often involves multisystem manifestations, including pulmonary fibrosis, hypertension and neurofibromas in the larynx and oropharynx, leading to airway challenges. This case report highlights the anaesthesia and airway management of a 48-year-old male with NF1 and a large parapharyngeal mass causing hoarseness, dysphagia and airway compromise, displacing major neck structures; he was posted for excision of the parapharyngeal mass. Indirect videolaryngoscopy during preoperative evaluation showed a funnel-shaped epiglottis, significant oedema of the surrounding tissues and a fixed left vocal cord, with a Mallampati score of IV. Fibreoptic intubation was initially planned; however, elective fibreoptic intubation might fail even with prior recognition of intraoral pathology due to grossly distorted anatomy and bleeding from trauma. Utilising the airway preparation carried out for fibreoptic intubation, videolaryngoscopy using C-MAC (Karl Storz GmbH & Co. KG, Germany) was performed to assess the feasibility of intubation under sedation and spontaneous respiration, which yielded a Percentage of Glottic Opening (POGO) score of 50%, corresponding to a Modified Cormack and Lehane grade of 2b. The possibility of pressure effects was ruled out, as the tumour was located laterally. After assessing the possibility of intubation with C-MAC, nasal intubation was successfully achieved using a size 6.5 flexometallic tube under deep sedation, following the administration of Inj. Midazolam 1 mg, Inj. Fentanyl 80 μg, and Inj. Propofol 1 mg/kg. The tumour was excised without complications and the patient was extubated uneventfully. This report emphasises the importance of preoperative planning and a stepwise, adaptable approach to airway management in such complex scenarios.